2012
DOI: 10.5194/bg-9-2603-2012
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary phosphorus and iron cycling in and below the oxygen minimum zone of the northern Arabian Sea

Abstract: Abstract. In this study, we investigate phosphorus (P) and iron (Fe) cycling in sediments along a depth transect from within to well below the oxygen minimum zone (OMZ) in the northern Arabian Sea (Murray Ridge). Pore-water and solid-phase analyses show that authigenic formation of calcium phosphate minerals (Ca-P) is largely restricted to where the OMZ intersects the seafloor topography, likely due to higher depositional fluxes of reactive P. Nonetheless, increased ratios of organic carbon to organic P (C org… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 89 publications
(111 reference statements)
5
108
1
Order By: Relevance
“…and increased with increasing bottom water oxygenation. Pore water profiles, 210 Pb dating and Ti/Ca ratios of sediments from the same locations showed that sedimentation was relatively continuous with no evidence for winnowing or gravity flows (Kraal et al, 2012).…”
Section: Oxygen Concentrations Total Organic Carbon Content (Toc) Anmentioning
confidence: 99%
“…and increased with increasing bottom water oxygenation. Pore water profiles, 210 Pb dating and Ti/Ca ratios of sediments from the same locations showed that sedimentation was relatively continuous with no evidence for winnowing or gravity flows (Kraal et al, 2012).…”
Section: Oxygen Concentrations Total Organic Carbon Content (Toc) Anmentioning
confidence: 99%
“…This rate of CFA growth is high compared to high-productivity deep-sea settings (34), but is within the range of high-productivity continental margin settings [4,7]. These downcore records of CFA P might also be influenced to some degree by variation in the input of dust through time; dust in this region contains some CFA [22], which would presumably be delivered to the seafloor with little or no geochemical alteration before burial [2].…”
Section: Implications For P Burial In Continental Margin Sedimentsmentioning
confidence: 99%
“…In particular, earlier scenarios called for the vast majority of reactive P sedimentation to the seafloor to be in the form of organically-bound P compounds. A variety of studies focusing on low-oxygen environments note somewhat higher-than-Redfield ratios in the organic matter fraction [19], but also find a significant role of iron in the burial and diagenetic cycle of P [20][21][22][23]. This dialog, and a satisfactory understanding of coupled C and P cycling in modern environments, can be informed by continued detailed studies focused on environments that receive similar sedimentary inputs but span a range of oxygen contents to clarify the role of oxygenation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations